Metallopeptidades 2 and 9 genes epigenetically modulate equine endometrial fibrosis - Alpoim-Moreira, Joana; Fernandes, Carina; Pimenta, Jorge; Bliebernicht, Miguel; Rebordão, Maria Rosa; Castelo-Branco, Pedro; Szóstek-Mioduchowska, Anna; Skarzynski, Dariusz J.; Ferreira-Dias, Graça (Frontiers in Veterinary Science, 2022)
Endometrium type I (COL1) and III (COL3) collagen accumulation, periglandular fibrosis and mare infertility characterize endometrosis. Metalloproteinase-2 (MMP-2), MMP-9 and tissue inhibitors of metalloproteinases (TIMP-1 and TIMP-2) are involved in collagen turnover. Since epigenetic changes may control fibroproliferative diseases, we hypothesized that epigenetic mechanisms could modulate equine endometrosis. Epigenetic changes can be reversed and therefore extremely promising for therapeutic use. Methylation pattern analysis of a particular gene zone is used to detect epigenetic changes. DNA methylation commonly mediates gene repression. Thus, this study aimed to evaluate if the transcription of some genes involved in equine endometrosis was altered with endometrial fibrosis, and if the observed changes were epigenetically modulated, through DNA methylation analysis. Endometrial biopsies collected from cyclic mares were histologically classified (Kenney and Doig category I, n = 6; category IIA, n = 6; category IIB, n = 6 and category III, n = 6). Transcription of COL1A1, COL1A2, COL3A1, MMP2, MMP9, TIMP1 and TIMP2 genes and DNA methylation pattern by pyrosequencing of COL1A1, MMP2, MMP9, TIMP1 genes were evaluated. Both MMP2 and MMP9 transcripts decreased with fibrosis, when compared with healthy endometrium (category I) (P < 0.05). TIMP1 transcripts were higher in category III, when compared to category I endometrium (P < 0.05). No differences were found for COL1A1, COL1A2, COL3A1 and TIMP2 transcripts between endometrial categories. There were higher methylation levels of (i) COL1A1 in category IIB (P < 0.05) and III (P < 0.01), when compared to category I; (ii) MMP2 in category III, when compared to category I (P < 0.001) and IIA (P < 0.05); and (iii) MMP9 in category III, when compared to category I and IIA (P < 0.05). No differences in TIMP1 methylation levels were observed between endometrial categories. The hypermethylation of MMP2 and MMP9, but not of COL1A1 genes, occurred simultaneously with a decrease in their mRNA levels, with endometrial fibrosis, suggesting that this hypermethylation is responsible for repressing their transcription. Our results show that endometrosis is epigenetically modulated by anti-fibrotic genes (MMP2 and MMP9) inhibition, rather than fibrotic genes activation and therefore, might be promising targets for therapeutic use.